The Importance of Tutoring Activities in Reducing Student Learning Difficulties in an Elementary School Environment - T, Harmi; Jatiyasa, I Wayan (International Journal of Multidisciplinary Sciences, 2024)
The number of children who experience difficulties in learning causes children not to develop according to their capacity. This is usually due to interference, both from internal student factors which are limited to intelligence factors and external student factors. There are two types of learning difficulties, namely pre-academic learning difficulties including: motor and perceptual disorders, cognitive learning difficulties, language development disorders, and difficulties in completing social behavior. While academic learning difficulties include difficulties in reading, writing, and arithmetic. In overcoming these problems, it is important to conduct tutoring in reducing student learning difficulties in the elementary school environment. The purpose of this study was to determine the description of the implementation of tutoring services in reducing the learning difficulties of elementary school students in Amparita village. The research location is Independent Tutoring in Amparita Village. This selection is related to the characteristics of the research subjects, namely tutoring mentors who have a Bachelor of Education background who have implemented tutoring services. The research method used a qualitative descriptive research approach. Data collection techniques were carried out by observation, interviews, and documentation studies. The result of the research is that the implementation of tutoring services can help students reduce learning difficulties. The tutoring services provided are integrated with the subject matter (when learning takes place), so that no specific service material is prepared but the mentor provides students with material according to the lessons at school. In its implementation, sometimes the mentor provides it with a cooperative learning model so that students can learn from each other and share with other students to achieve the goals of a particular learning. The success of the implementation of tutoring services in reducing learning difficulties is that students show an increased interest in learning, do and collect assignments on time and can concentrate by paying attention to the subject matter provided by the teacher.